Bevacizumab as First-line Treatment for HER2-negative Advanced Breast Cancer: Paclitaxel plus Bevacizumab Versus Other Chemotherapy - NAKAMOTO, SHOGO (In Vivo, 2020)
Background: The efficacy of paclitaxel and bevacizumab (PB) compared with other chemotherapies in patients with human epidermal growth factor receptor 2-negative (HER2(−)) advanced breast cancer is unclear. Patients and Methods: We retrospectively investigated 301 patients with HER2(−) ABC who received first-line chemotherapy from January 2011 to December 2016. Results: We included 114 patients who received PB and 187 patients who received other chemotherapies. After propensity score matching, the PB group showed a significantly superior overall response rate (77.8% vs. 38.9%, p<0.0001) and median time to treatment failure (7.3 vs. 5.9 months, p=0.035). In subgroup analyses, PB improved the median overall survival of patients with pleural lesions or pulmonary lymphangiopathy (not reached vs. 18.9 months, p=0.037), and of patients with three or more metastatic sites without liver metastases, (48.0 vs. 27.3 months, p=0.015). Conclusion: Compared with conventional chemotherapy, PB improved the overall response rate and time to treatment failure in patients with HER2(−) advanced breast cancer and improved overall survival in some patient subgroups.